How vital is the role of affect on post-adoption behaviors? An examination of social commerce users. (June 2018) - Osatuyi, Babajide; Qin, Hong
Highlights: Theoretically proposed an integrated model of social commerce post-adoption behaviors. Empirically tested two competing theoretical views of post-adoption outcomes in the social commerce context. Satisfaction partially mediates social and hedonic gratifications effect on post-adoption outcomes. Satisfaction fully mediates utilitarian gratifications effect on post-adoption outcomes. Abstract: Social commerce describes a new trend and fast-growing e-commerce business model that utilizes social connections in social networking to promote commerce in the online space. Despite its growth much is not known about factors that motivate users beyond their initial adoption to engage in post-adoption behaviors such as continuance intention to use social commerce to the point of becoming addictive users. Two predominant views have been used to study social commerce in the literature; one emphasizes the role of affect on behavioral outcomes (i.e., dual processing view) while the other suggests that affect is not important in use decisions (i.e., the independency view). Moreover, both views offer inconsistent results on understanding how consumers use social commerce sites. To address this inconsistency in the literature, this paper proposes and empirically evaluates a model that integrates the existing views to extend our understanding on social commerce post-adoption behaviors. Based on existing literature, this study identifies social, hedonic, and utilitarian gratifications that social commerce users seek to fulfill on social commerce sites. A cross-section of 510 social commerce users were recruited to report their perceptions on social commerce usage. Results indicate that the integrated model outperforms each of the dominant views in terms of explaining continuance use intentions and addictive behaviors. Satisfaction was found to both fully and partially mediate the relationship between perceived gratifications and their behavioral outcomes on social commerce sites.